Neural correlates underpinning synchronized movement of double scull rowers - Takahiro Hirao (Nature Portfolio, 2021)
Abstract We investigated the neural correlates underpinning synchronized movement in rowers using a neural index for social interaction termed the phi complex. Phi 1 and phi 2 indicate the enhancement and reduction of mirror neuron activation, respectively. We hypothesized that in a leader–follower relation, followers would exhibit a larger phi 2 power than leaders due to enhanced mirror neuron activation by the followers to accurately mimic their partner’s movements. We also expected that brain activation underlying social interaction would be enhanced during synchronization. Although phi 2 was not modulated by role (leader vs. follower) or condition (usual-pair vs. unusual-pair), the statistical analysis suggested the relationship between the magnitude of phi 2 and empathetic ability in followers in the usual-pair condition. Given that the activation of the mirror neuron system underlies empathic ability, it is plausible that the participants used the mirror neuron system to follow the movement of a usual partner. In other words, the leader in the synchronization did not need to use the mirror neuron system, which was consistent with the result of a larger phi 1 for leading than following the movement. These results suggest that the neural correlates of empathy may be used to synchronize with partners as the follower.